A study on the enforcement of illegal trading on pangolin under the Malaysian law / Mohd Suharin Sulaiman Siew …[et al.] - Sulaiman Siew, Mohd Suharin; Mustafa, Norhamizah; Mohd Noh, Hafatin Natrah; Mohd Yusof, Aimi Farhana; Said, Nur Diyana Munira (2010)
This research is a study on illegal trade of pangolin in Malaysia. The purpose of this research is to analyze the comprehensiveness of the existing laws in governing illegal trading of pangolin in Malaysia, to compare the enforcement of illegal trading of pangolin between United States and Malaysia and also to make recommendations as to how enforcement of illegal trading of pangolin should be governed in Malaysia. This is all due to, despite having laws in governing illegal trading of wildlife, but the number of illegal trade of pangolin is still increasing from time to time. Because of this, pangolin is threatened to extinct as the population of pangolin has been declining over the years. The Protection of Wildlife Act 1972 is not effective in governing the issue of illegal trading in Malaysia and this particular law needs to be amended in order for it to work effectively in protecting the wildlife.